Hyperbaric oxygen therapy is well tolerated and effective for ulcerative colitis patients hospitalized for moderate–severe flares: a phase 2A pilot multi-center, randomized, double-blind, sham-controlled trial. (October 2018) - Dulai, Parambir; Buckey, Jay; Raffals, Laura; Swoger, Jason; Claus, Paul; O'Toole, Kevin; Ptak, Judy; Gleeson, Michael; Widjaja, Christella; Chang, John; Adler, Jeffery; Patel, Nihal; et al.
Abstract BACKGROUND Hyperbaric oxygen therapy (HBOT) markedly increases tissue oxygen delivery. Case series suggest it may have a potential therapeutic benefit in ulcerative colitis (UC). We investigated the therapeutic potential of HBOT as an adjunct to steroids for UC flares requiring hospitalization. METHODS The study was terminated early due to poor recruitment with 18 of the planned 70 patients enrolled. UC patients hospitalized for moderate–severe flares (Mayo score ≥6, endoscopic sub-score ≥2) were block randomized to steroids + daily HBOT (n = 10) or steroids + daily sham hyperbaric air (n = 8). Patients were blinded to study assignment, and assessments were performed by a blinded gastroenterologist. Primary outcome was the clinical remission rate at study day 5 (partial Mayo score ≤2 with no sub-score >1). Key secondary outcomes were: clinical response (reduction in partial Mayo score ≥2, rectal bleeding sub-score of 0–1) and progression to second-line therapy (colectomy or biologic therapy) during the hospitalization. RESULTS A significantly higher proportion of HBOT-treated patients achieved clinical remission at study day 5 and 10 (50 vs. 0%, p = 0.04). HBOT-treated patients less often required progression to second-line therapy during the hospitalization (10 vs. 63%, p = 0.04). The proportion requiring in-hospital colectomy specifically as second-line therapy for medically refractory UC was lower in the HBOT group compared to sham (0 vs. 38%, p = 0.07). There were no serious adverse events. CONCLUSION In this small, proof-of-concept, phase 2A trial, the use of HBOT as an adjunctive therapy to steroids for UC patients hospitalized for moderate–severe flares resulted in higher rates of clinical remission, and a reduction in rates of progression to second-line therapy during the hospitalization. Larger well-powered trials are needed, however, to provided definitive evidence of therapeutic benefit.